On Testing the Adequacy of the Logistic Model Based on Negative Cumulative Extropy - Alizadeh Noughabi, Hadi; Shafaei Noughabi, Mohammad (Statistics, Optimization & Information Computing, 2025)
The logistic distribution has been used for various growth models, and is used in a certain type of regression, known appropriately as logistic regression. In this article, we propose a new goodness of fit test for the logistic distribution based on the negative cumulative residual extropy introduced by Tahmasebi and Toomaj (2022). The mean, variance and the other properties of the test statistic is presented. Percentage points of the test statistic are obtained and then power of the test against different alternatives are reported. The results of a simulation study show the test is competitive in terms of power. The proposed statistic is easy to compute and a real data set is used to illustrate the application of the proposed test.